2021
DOI: 10.1088/1361-6595/abf321
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the role of dielectric trap states on capacitively coupled radio-frequency plasma discharge: dynamic charging behaviors

Abstract: The influence of charge trap states in the dielectric boundary material on capacitively coupled radio-frequency (RF) plasma discharge is investigated with theory and particle-in-cell/Monte Carlo collision simulation. It is found that the trap states of the wall material manipulated discharge properties mainly through the varying ion-induced secondary electron emission (SEE) coefficient in response to dynamic surface charges accumulated within the solid boundary. A comprehensive SEE model considering surface ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…In fact, in the experimental study of Tschiersch et al 66 , the effective secondary electron emission coefficients for different dielectric materials have been reported to be between 0.02 and 0.4. Values of that order have been calculated theoretically through solid-state considerations for dielectric surfaces 67 and through quantum-kinetic methods for metallic surfaces 68 , as well as measured for metallic surfaces 69 . The surface charge density on the surface of the dielectrics is obtained by integrating charged particle fluxes to the surface in time.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, in the experimental study of Tschiersch et al 66 , the effective secondary electron emission coefficients for different dielectric materials have been reported to be between 0.02 and 0.4. Values of that order have been calculated theoretically through solid-state considerations for dielectric surfaces 67 and through quantum-kinetic methods for metallic surfaces 68 , as well as measured for metallic surfaces 69 . The surface charge density on the surface of the dielectrics is obtained by integrating charged particle fluxes to the surface in time.…”
Section: Methodsmentioning
confidence: 99%
“…The ion-induced SEE coefficient is independent of the incident ion temperature (only true for cold ion) and is a constant once the wall material is fixed. Recent theories showed that the accumulated surface charges in dielectric materials can modify the ion-induced SEE coefficient [43]. The present study focuses on a metallic boundary, hence the ion-induced SEE coefficient remains constant.…”
Section: Electron Sheath Modeling Considering the Plasma-surface Inte...mentioning
confidence: 92%
“…A significant fraction of the applied voltage drops across the charged wafer reducing the voltage drop across the plasma [13,19,20]. Furthermore, the charge state of the dielectric surface, depending on the specific wafer material, can significantly influence the plasma particle impact induced secondary electron emission probabilities, as it was discussed recently [21]. The secondary electron emission yields, including both electron and ion impact induced processes, can significantly affect the discharge properties, especially at high voltage and low pressure conditions, most relevant to etching applications [22].…”
Section: Introductionmentioning
confidence: 99%